(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
The study is carried out to predict stature from upper limb anthropological measurements. Forensic anthropology is the application of anthropological knowledge in criminal investigation. So far, there are studies conducted to estimate stature from hand measurements, but from this region of Uttarakhand, studies are lacking. Such a study can assist in the identification of deceased individuals whose remains are decomposed, burned, mutilated or otherwise unrecognisable. In this study, attempt will be made to find the correlation between stature and hand dimension. The identification of individual from skeletal remains and badly decomposed or otherwise unidentified human remains is important in both legal and humanitarian contexts and also to give closure.